The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1653/024.098.0323
|View full text |Cite
|
Sign up to set email alerts
|

The Abundance of Specialist and Generalist Lepidopteran Larvae on a Single Host Plant Species: Does Spatial Scale Matter?

Abstract: Specialist insects are more sensitive to spatial variations than generalists, which are able to exploit diverse hosts in various habitats. This study investigated whether specialist lepidopteran larvae feeding on a single host, Roupala montana Aubl. (Proteales: Proteaceae), maintain consistent abundance rates across spatial scales. We compared the abundance of specialist and generalist larvae at local and regional scales during the same period of collection, with equal sample efforts, and in the same type of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
1
0
2
Order By: Relevance
“…In addition, H. opalizalis was more abundant than P. phoenicealis on O. basilicum in the present study. This result corroborates with Braga & Diniz (2015), who observed that, in general, larvae of specialist folivorous lepidopteran were present at higher densities on a single specific host plants (Roupala montana Aubl.) than generalist ones.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In addition, H. opalizalis was more abundant than P. phoenicealis on O. basilicum in the present study. This result corroborates with Braga & Diniz (2015), who observed that, in general, larvae of specialist folivorous lepidopteran were present at higher densities on a single specific host plants (Roupala montana Aubl.) than generalist ones.…”
supporting
confidence: 91%
“…Thus, further studies should be conducted to investigate the potential of H. opalizalis and P. phoenicealis to become a pest of the sweet basil crop in Brazil, such as those that assess the biological parameters and degrees of specialization or polyphagia of these noctuid species at the population, community, and individual levels (Braga & Diniz 2015).…”
mentioning
confidence: 99%
“…Es importante considerar que si bien los resultados fueron en general positivos, existen una serie de factores que también pueden ser decisivos en el éxito del programa de manejo de la plaga. El tipo de suelo, la diversidad de las plantas asociadas, la amplitud de la dieta de los insectos plaga, la composición química y física de las plantas huésped, la abundancia de enemigos naturales, y los micro y macro climas presentes en cada área que influyen en la abundancia de la polilla en cada ciclo de cultivo y que se deben considerar para el control biorracional de la plaga [16][17][18] .…”
Section: Discussionunclassified
“…O conhecimento dessa diversidade é resultado principalmente de estudos com adultos como, por exemplo, listas de espécies e revisões taxonômicas (EMERY et al, 2006;FERRO;DINIZ, 2007;BOGIANI et al, 2012;SCHERRER et al, 2013). Sendo assim, há relativamente poucos estudos sobre os estágios imaturos dos Lepidoptera do Cerrado (e. g. MUNIZ et al, 2012;BÄCHTOLD et al, 2013;DINIZ et al, 2013;BRAGA;DINIZ, 2015).…”
Section: Introdução Geralunclassified